2014
DOI: 10.4103/0972-0707.128052
|View full text |Cite
|
Sign up to set email alerts
|

Computed tomography evaluation of residual root thickness after pre-flaring using gates Glidden drills: The sequence effect

Abstract: Aim:The aim of the present study is to evaluate the residual root thickness in mesiolingual (ML) canals of mandibular molars after pre-flaring using different sequences of Gates-Glidden (GG) drills.Materials and Methods:Computed tomography (CT) scans of the ML canals of 60 mandibular first molars were provided from areas within 1, 2, 3 and 4 mm of the furcation area and minimum initial root thickness (MIRT) of concave areas was measured at each level. The samples were divided into two groups (G1 and G2) which … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
2
0
3

Year Published

2014
2014
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 24 publications
0
2
0
3
Order By: Relevance
“…Numerous studies have compared the Ni-Ti files,[ 17 19 ] but few have evaluated coronal enlargers. [ 20 21 22 ] The aim of this study was to evaluate the minimum residual root thickness (MRRT) of danger zone after canal preparation using GG drills, ProTaper and RaCe rotary files in MB canals of mandibular first molars by cone beam computerized tomography (CBCT).…”
Section: Introductionmentioning
confidence: 99%
“…Numerous studies have compared the Ni-Ti files,[ 17 19 ] but few have evaluated coronal enlargers. [ 20 21 22 ] The aim of this study was to evaluate the minimum residual root thickness (MRRT) of danger zone after canal preparation using GG drills, ProTaper and RaCe rotary files in MB canals of mandibular first molars by cone beam computerized tomography (CBCT).…”
Section: Introductionmentioning
confidence: 99%
“…They reported the incidence rates of 5% and 2% for transportation and perforation in the 8-step technique, respectively, and frequency rates of 17%, 7% and 6% for transportation, perforation and canal obstruction in the step-back technique, respectively. To verify the effect of canal shape on the incidence of error, Yin et al, [ 22 ] demonstrated that in the curved canals, the rotary and manual systems manifested different performance regarding the incidence of error and cleaning the surface of the canal.…”
Section: Discussionmentioning
confidence: 99%
“…O desgaste compensatório favorece também a remoção de tecido infectado e a mecânica de irrigação dos fluidos. (BUSQUIM; DOS SANTOS, 2002;GULABILAVA et al, 2010;LAZZARETTI et al, 2006; WU; VAN DER SLUIS;WESSELINK, 2005) Estrela et al (1990 relataram que o uso das brocas de GG #3 a 2 a 3 mm da furca proporcionaram desgaste significativos, ocorrendo um caso de perfuração, enquanto Akhlaghi et al (2015) avaliaram a espessura da raiz residual da zona de risco após o pré-alargamento do canal MV dos primeiros molares inferiores, utilizando: Protaper ® , Race ® e Gates Glidden. Os dentes foram avaliados com auxílio da tomografia computadorizada com feixe cônico (CBCT).…”
Section: Discussionunclassified
“…(ESTRELA et al, 1990;ISOM;MARSCHALL;BAUMGARTNER, 1995;KUTTLER et al, 2004) E há ainda aqueles que defendem o uso dessas brocas para a realização do preparo do canal, afirmando serem seguras quando usadas adequadamen-te. (AKHLAGHI et al, 2015;COUTINHO FILHO et al, 2001;WU;VAN DER SLUIS;WESSELINK, 2005) Em alguns trabalhos, as brocas de Gates Glidden promovem desgastes significativos na zona de risco, porém sem relato de perfurações. (COUTINHO FILHO et al, 2001;PALO et al, 2006).…”
Section: Discussionunclassified
See 1 more Smart Citation